Customer Saving Satisfaction Viewed from the Customer’s Perspective: A Study on Islamic Banks in the Special Region of Yogyakarta - Widyarini Widyarini; Syamsul Hadi (Millah: Journal of Religious Studies, 2021)
Technological developments already change the behavior of employee salary payments. This is done to reduce the risk of carrying large amounts of cash, speeding up the payment process and reduce the working time of the finance department. Sometimes a spesific bank appointment does not make employees feel satisfied for several reasons, such as: already a customer from another bank, forced to open a new account, short of bank facilities (ATMs), ATM the location is far from his or her the house. The purpose of the research is to find out the difference in customer satisfaction levels of saving customers reviewed from the beginning of bank account opening, termed 'Voluntary Customer' or 'Forced Customer'. This research is a field study with the population of Saving Customers in Sharia Bank operating in the Special Region of Yogyakarta. Samples are taken by snowball sampling method. The number of samples that met the requirements was 394 consist of 'Voluntary Customer' as many as 247 respondents and 'Forced Customer' as many as 147 respondents. The questionnaire was set in five points Likert scales. Validity Test using Product Moment Correlation and Reliability Test using Chronbah Alpha. The results of the study are as follows: 1). Customer satisfaction of Sharia Bank is still very low. 2). There is a significant difference between the satisfaction of 'Voluntary Customer' and 'Forced Customer'. 3) There is a significant difference between the satisfaction of 'Voluntary Customers who know the contract' and 'Forced Customers who do not know the contract'. 4). There is no significant difference between the satisfaction of 'Voluntary Customer who knows the contract' and 'Voluntary Customer who does not know the contract'. 5). There is no significant difference between the satisfaction of 'Forced Customer who knows the contract' and 'Forced Customer who does not know the contract'. 6). There is no significant difference between the satisfaction of 'Voluntary Customers who do not know the contract' and the 'Forced Customer who knows the contract'.